ANALISIS IMPLEMENTASI KEBIJAKAN TAX AMNESTY DALAM UPAYA MENINGKATKAN KEPATUHAN WAJIB PAJAK - Ardita Nurul Inayah (JURNAL LENTERA AKUNTANSI, 2018)
ABSTRACT State revenue from the tax sector is still low. Low tax revenues lead to low economic growth as well. To increase government tax revenue make a policy that is Tax Amnesty (forgiveness) tax. Tax Amnesty is expected to increase state revenue and increase voluntary compliance to the tax administration system because by becoming part of the tax amnesty, the taxpayer will not be able to avoid the obligation in the payment of taxation. This research is intended to see how much Tax Amnesty policy in increasing compliance taxpayer. The research method used is descriptive qualitative method, is a method that provides an overview of the object of research through the data collected. The data in this study comes from the data or documents that exist in the tax director general. The result of data analysis found that: (1) Taxpayer compliance level that submitted SPT of 64,263% for year 2016, increasing 3,989% compared to 2015 (60,274%). This is due to the Tax Amnesty program. (2) Taxpayers who utilize Tax Amnesty until the end of 2016 amounted to 21.2626% this is due to the lack of government socialization to taxpayers regarding Tax Amnesty. (3) Realization of tax revenue in 2016 amounted to 64.27% decreased compared to 2015 (67.76%). However, the 2016 ppajak target is raised from 2015 by 1,294.258 trillion to 1,355.203 trillion by 2016. The results of this study indicate that Tax Amnesty policy provides an increase to taxpayer compliance even though the realization of tax revenue has decreased compared to last year.Keyword: Policy, Tax Amnesty